Systemic neonatal candidiasis. - Reid, M. (Ulster Medical Society, 1991)
Forty-five cases of systemic neonatal candidiasis were diagnosed over a 9-year period in a neonatal intensive care unit; 42 infants weighted less than 1.5 kg. All had been very ill with preceding bacterial sepsis and other complications of low birthweight. Where treatment was instituted the mortality was low (4 out of 39 dying) and complications of treatment were transitory. We therefore recommend diligent examination for the presence of this infection, and treatment with a combination of amphotericin B and 5-flucytosine.